2014
DOI: 10.1073/pnas.1416737111
|View full text |Cite
|
Sign up to set email alerts
|

Structural and energetic determinants of adhesive binding specificity in type I cadherins

Abstract: Type I cadherin cell-adhesion proteins are similar in sequence and structure and yet are different enough to mediate highly specific cell-cell recognition phenomena. It has previously been shown that small differences in the homophilic and heterophilic binding affinities of different type I family members can account for the differential cell-sorting behavior. Here we use a combination of X-ray crystallography, analytical ultracentrifugation, surface plasmon resonance and double electron-electron resonance (DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 46 publications
9
108
1
Order By: Relevance
“…S1), yielding heterophilic K D s ranging between 3.6 and 43.9 μM (Fig. 1C), similar to the affinities of other tight-binding cell adhesion molecules (22)(23)(24)(25)(26)(27)(28). Interestingly, the strongest-binding pairs (Dsg1:Dsc1 and Dsg4:Dsc1) correspond to those expressed in the outermost layers of human skin, and the weakest (Dsg3:Dsc3) to those restricted to basal layers (1,10), consistent with a potential role for differential affinities in maintenance of cell arrangement in stratified epithelia (1).…”
Section: Significancesupporting
confidence: 62%
“…S1), yielding heterophilic K D s ranging between 3.6 and 43.9 μM (Fig. 1C), similar to the affinities of other tight-binding cell adhesion molecules (22)(23)(24)(25)(26)(27)(28). Interestingly, the strongest-binding pairs (Dsg1:Dsc1 and Dsg4:Dsc1) correspond to those expressed in the outermost layers of human skin, and the weakest (Dsg3:Dsc3) to those restricted to basal layers (1,10), consistent with a potential role for differential affinities in maintenance of cell arrangement in stratified epithelia (1).…”
Section: Significancesupporting
confidence: 62%
“…Next, we used MD simulations to investigate the molecular determinants of cadherin conformational interconversion. Since only the EC1-EC2 domains are involved in trans binding, we used four EC1-EC2 trans dimer crystal structures in our simulations: (i) WT cadherin (PDB ID code 2QVF), (ii) mutant W2A (PDB ID code 3LNH), which replaces the swapped Trp with an Ala and traps cadherin in an X-dimer conformation (12), (iii) mutant K14E (PDB ID code 3LNE), which eliminates a key salt bridge in the X-dimer interface and traps cadherin in an S-dimer structure (12), and (iv) W2F, "conformational-shuttling" mutant (PDB ID code 4NUQ), which relieves the strain in the swapped N-terminal β-strand and forms weak binding affinity S-dimers (37); previous DEER experiments showed that this W2F mutant construct populates an equilibrium ensemble of X-dimers and S-dimers (21). All structures used in these simulations were from Ecad except the W2F mutant, which was from N-cadherin (Ncad), a closely related type I classical cadherin that shares a high sequence identity (∼77%) of its N-terminal β-strand with Ecad (∼53% sequence identity over the whole EC1-EC2 dimer structure), with conserved amino acids forming the swapping interface.…”
Section: Cadherin Energy Landscape and Transition Pathway For The Intmentioning
confidence: 99%
“…The change in torsional angle between the EC1 domains in the W2F mutant was more abrupt (Fig. 4D, black line), likely due to both the smaller Phe2 side chain and fewer interactions at the dimer interface (21,37). In comparison, the bigger Trp2 indole ring occupied a larger surface area in the hydrophobic pocket of WT-Ecad dimers and was additionally stabilized by a hydrogen bond formed between its side chain NH group and the Asp90 carbonyl group in the hydrophobic pocket (10,17,37).…”
Section: Intermediate Dimer States Exhibit Force-induced Conformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical cadherins have a homophilic binding property that allows homogeneous cells to be organized into an independent solid tissue such as an epithelium (Nose et al, 1990;Takeichi, 1991;Vendome et al, 2014). Within the tissue, the extracellular bonds formed between the paired cadherins are thought to transmit forces originating from intracellular actomyosin activities that are required for epithelial homeostasis and morphogenesis (Borghi et al, 2012;Guillot and Lecuit, 2013;Heisenberg and Bellaïche, 2013;Takeichi, 2014).…”
Section: Introductionmentioning
confidence: 99%